Condition of T- and B-cellular-mediated specific protection in sows and their offspring subject to essential oils - PrudyusТ. Y.; Vishchur, O. I.; Mudrak, D. B.; KentsaloY. І.; Holubieva, T. A.; Gutsol, N. V. (Regulatory Mechanisms in Biosystems, 2024)
The objective of the study was identification of the activities of T- and B-cellular mechanisms of specific protection in sows and their offspring subject to essential oil from Origanum vulgare, cinnamaldehydum, extract from Capsicum sp., Rosmarinus officinalis, and Thymus serpyllum in the form of encapsulated feed supplement Aktyvno. The assessment of the activity of the cellular factors of the specific protection was conducted by enumerating T- and B-lymphocytes and assessing their functional ability in peripheral blood of swine in the reaction of spontaneous rosette-formation with ram erythrocytes. For the study, we selected Large White sows, of the English PIC genetics, and divided them into two groups (control and experimental, 10 animals in each). Experimental Group sows, for a month prior to the expected labor and until day 28 of lactation, received the Aktyvno feed supplement together with their standard diet, in the amount of 0.1 kg/t of fodder, and Control Group animals received only the standard mixed feed. The piglets born from the sows of Experimental and Control groups, starting from the age of 5 days and until weaning, received pre-starter mixed feed (PMF). During the same period, the piglets of the Experimental Group had been additionally receiving Aktyvo in the amount of 0.2 kg/t of mixed feed. To conduct the immunological studies, we collected blood of the sows from the jugular vein on days 85 and 112 of farrow and day 21 of lactation. From the piglets, blood samples were collected from the superior vena cava, when the animals were 5, 14, and 28 day-old. The numbers of T- and B-lymphocytes and their functional activities in heparin-stabilized blood were determined using the rosette formation method (E-rosette forming lymphocytes and erythrocyte-antibody-complement rosette forming lymphocytes, E-RFLs and EAC-RFLs). In the sows, intake of the tested essential oils led to increase in the number of T-lymphocytes (total and theophylline-resistant) and increase in their functional activity through redistribution of the avidity of the cells’ receptor field, in particular, increase in the numbers of low-avid T- and B-lymphocytes and decline in functionally inactive T-lymphocytes. At the same time, in Experimental Group sows on day 112 of farrow and day 21 of lactation, we observed a high number of theophylline-resistant T-lymphocytes with low density of receptors and lower number of inactive Th-lymphocytes in the blood. In the piglets born from the sows of Experimental Group and Control, we observed similar changes, although they were manifested in much lower degree. At the same time, in the blood of 28 day-old Experimental Group piglets that had been consuming the Aktyvo supplement, we saw a lower number of inactive ТА-RFLs and higher number of theophylline-resistant T-lymphocytes with low avidity. Therefore, secondary plant components activate the cellular mechanisms of specific protection in the sows and their offspring, which in general promotes the formation of high immune potential of their bodies. The prospects of further studies include researching the influence of secondary plant components of O. vulgare, Cinnamomum sp., Capsium sp., R. officinalis, and T. serpyllum on the colostral mechanisms of protection in sows.